PENGEMBANGAN MEDIA PEMBELAJARAN PAPAN UANG HEBAT PADA PELAJARAN MATEMATIKA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS II DI SDIT AN-NISA - Setiawati, Harnum; Misbah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Low student learning outcomes can occur partly because of the lack of learning media used to facilitate students in learning. This research was conducted with the aim of developing great money board learning media to improve student learning outcomes. This research uses RnD research using the ADDIE model. The validity test was carried out by three experts, namely material experts with a percentage of 92.0%, media experts with a percentage of 94.0% and language experts with a percentage of 88.0%. Meanwhile, the results of student responses showed a percentage of 82.8% and teacher responses showed a percentage of 94%. So it can be concluded that the great money board learning media can be declared valid and suitable for use in the learning process. Meanwhile, in testing the effectiveness of media in improving learning outcomes, tests were carried out in the form of post-tests and pre-tests to obtain an N-Gain score of 0.782 which was included in the high category. So it can be stated that the great money board learning media is effectively used in the classroom learning process.